Independent Labour Party records, 1893-1960. - Independent Labour Party (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2015)
These records cover the formation and early years of the Independent Labour Party in some detail. They include iconic moments, such as the first Conference in Bradford and the formation of the Labour Representation Committee in 1906. They also reveal the changing aspirations of the Party as it moved from being a hopeful form of protest, to working within a Labour Party that could run the country. One of the more striking elements of these reports is the fact that it was felt necessary to have an Intelligence Department prior to 1905;" embryonic as the venture was then, it was evidently felt that information would be key to its success. War was one of the societal aberrations that the Independent Labour Party found to be the most deplorable; the Boer War and World War One were seen as both needless sources of death for the young and weapons by which the Government could sweep aside labour reforms that Party Members had fought for throughout many previous years. The I.L.P.'s objections to war would, in time, bring it into contact with the No Conscription Fellowship, to the extent that it sent a delegate to at least one of their meetings. These papers also cover the foundation of the I.L.P. Press and details of its growing range of publications including their authors and dates. In the latter 1920's and early 1930's, growing tensions between the I.L.P and the Labour Party it helped to form, would lead to an irreparable split. This split pitted the Independent Labour Party against the Labour Party, but the latter was so well established at this point as to continue without the former. The I.L.P. lost a great deal of its Membership in the split and went into a decline from which it has never truly recovered. It has continued to campaign though and does still, for more tolerance and a questioning of the perceived political dogma of the time. The original papers, which have been published here, are currently held at the London School of Economics and Political Science.
Date range: 1893-1960.
Keywords: Independent Labour Party -- History -- 19th century; Independent Labour Party -- History -- 20th century